2020
DOI: 10.1002/pld3.244
|View full text |Cite
|
Sign up to set email alerts
|

Biosynthesis of cyanogenic glucosides in Phaseolus lunatus and the evolution of oxime‐based defenses

Abstract: Lima bean, Phaseolus lunatus, is a crop legume that produces the cyanogenic glucosides linamarin and lotaustralin. In the legumes Lotus japonicus and Trifolium repens, the biosynthesis of these two α‐hydroxynitrile glucosides involves cytochrome P450 enzymes of the CYP79 and CYP736 families and a UDP‐glucosyltransferase. Here, we identify CYP79D71 as the first enzyme of the pathway in P. lunatus, producing oximes from valine and isoleucine. A second CYP79 family member, CYP79D72, was shown to catalyze the form… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
17
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2
2

Relationship

2
8

Authors

Journals

citations
Cited by 24 publications
(19 citation statements)
references
References 56 publications
0
17
0
Order By: Relevance
“…In recent decades, advances in genomics, combined with biochemical and physiological studies, have provided important insights into the molecular bases of these defense metabolite pathways and their macroevolutionary origins (e.g. Zhuang et al ., 2012; Edger et al ., 2015; Xu et al ., 2017; Lai et al ., 2020). On a microevolutionary timescale, species that are polymorphic for chemical defense production have served as especially valuable systems for studying the molecular basis of adaptive variation and the roles of natural selection and other forces in maintaining it (Brachi et al ., 2015; Wager & Li, 2018; Keith & Mitchell‐Olds, 2019; Lowry et al ., 2019).…”
Section: Introductionmentioning
confidence: 99%
“…In recent decades, advances in genomics, combined with biochemical and physiological studies, have provided important insights into the molecular bases of these defense metabolite pathways and their macroevolutionary origins (e.g. Zhuang et al ., 2012; Edger et al ., 2015; Xu et al ., 2017; Lai et al ., 2020). On a microevolutionary timescale, species that are polymorphic for chemical defense production have served as especially valuable systems for studying the molecular basis of adaptive variation and the roles of natural selection and other forces in maintaining it (Brachi et al ., 2015; Wager & Li, 2018; Keith & Mitchell‐Olds, 2019; Lowry et al ., 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Cyanogenic glycosides are derived from the amino acids phenylalanine, tyrosine, valine, leucine, and isoleucine, and from the non-protein amino acid cyclopentenylglycine (Olafsdottir et al, 1991; Gleadow and Møller, 2014). The full biosynthetic pathway for cyanogenic glucosides has been characterized in several angiosperm species including sorghum ( Sorghum bicolor; (Koch et al, 1995; Bak et al, 1998b; Jones et al, 1999), cassava ( Manihot esculenta; Andersen et al, 2000; Jørgensen et al, 2011; Kannangara et al, 2011), barley ( Hordeum vulgare; Knoch et al ., 2016), Lotus japonicus (Forslund, 2004; Takos et al, 2011), Eucalyptus cladocalyx (Hansen et al, 2018), almond ( Prunus dulcis ; Thodberg et al, 2018) and green bean ( Phaseolus vulgaris; Lai et al, 2020), and has been partially identified in conifers (Luck et al, 2017). Comparison of the biosynthetic pathways reveal that the biosynthesis has arisen independently several times in the plant kingdom (Takos et al, 2011; Hansen et al, 2018; Thodberg et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…A T-DNA insertion in the CYP83B gene leads to plants with a phenotype of auxin overproduction, whereas CYP83B overexpression leads to the loss of apical dominance, typical of an auxin deficit [ 57 , 58 ]. In addition, in Phaseolus lunatus , CYP83E is involved in the biosynthesis of cyanogenic glucoside via indole aldoxime oxidation [ 59 ]. Although the biochemical function of DzCYP83F is still unknown and neither glucosinolates nor cyanogenic glucosides have been found in durian fruit, it potentially utilizes IAA as a substrate to maintain auxin homeostasis during durian fruit ripening.…”
Section: Resultsmentioning
confidence: 99%